1987
DOI: 10.1007/bf01296287
|View full text |Cite
|
Sign up to set email alerts
|

Comparative prevalence of gallstone disease at 100-year interval in a large Romanian town, a necropsy study

Abstract: The prevalence of gallstone disease in a large Romanian town was determined on 6275 necropsies performed during a 10-year period (1973-1982). The "crude" prevalence of gallstone disease in women was 17.1% and in men, 6.9%. Age-standardized prevalence was 8.4% in women and 5.0% in men. This rate is lower than the prevalence of gallstones in northern or central European countries, but it is higher than that established in some southern countries of Europe. A comparison of the "crude" prevalence of gallstone dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…The rate for females remained more or less stable ( Figure B). From the first three years to the last three years, the prevalence in men aged 50-59 years increased from 7% to 18% (0001<p<001, XI test), from 12% to 20% (0001<p<0-01) in men aged 60-69 years, and from 21% to 25% (0-05<p<0 10) in men aged 70-89 years. For women the corresponding changes in prevalence were from 28% to 24% in those aged 50-59 years (p>05), from 20% to 16% in those aged 60-69 years (04<p<05), and from 29% to 28% (p>0-5) in those aged 70-89 years.…”
Section: Resultsmentioning
confidence: 95%
“…The rate for females remained more or less stable ( Figure B). From the first three years to the last three years, the prevalence in men aged 50-59 years increased from 7% to 18% (0001<p<001, XI test), from 12% to 20% (0001<p<0-01) in men aged 60-69 years, and from 21% to 25% (0-05<p<0 10) in men aged 70-89 years. For women the corresponding changes in prevalence were from 28% to 24% in those aged 50-59 years (p>05), from 20% to 16% in those aged 60-69 years (04<p<05), and from 29% to 28% (p>0-5) in those aged 70-89 years.…”
Section: Resultsmentioning
confidence: 95%
“…It is supported by a Romanian necropsy study comparing 1873–82 with 1973–82 10. Its explanation is not clear, but the population is known to be heavier, which is a risk factor for cholelithiasis 15-17.…”
Section: Discussionmentioning
confidence: 98%
“…Necropsy studies have shown that, even after standardisation for age and sex, there are major differences between different countries (table 1). The available necropsy data, scrutinising longer intervals of time, decades1 2 or even a century,3 have revealed a trend of increasing gallstone prevalence.…”
Section: Epidemiologymentioning
confidence: 99%